Degradation-damage model application for landslide accumulation stability and reinforcement optimization in Southeast Xizang: a case study - Lv, Guangdong; Li, Wenwei; Wang, Baotian; Zuo, Jinyu; Wang, Jiahui (Frontiers in Earth Science, 2024)
This research develops an elastoplastic damage constitutive model incorporating the strain softening response of common engineering soil materials in southeastern Xizang to evaluate and optimize reinforcement solutions for highway-traversing landslide accumulations. Grounded in deterioration mechanics theory, the model characterizes the progressive strength loss and failure evolution of the soils. Verified and calibrated, it is numerically implemented in FLAC3D to simulate the stability conditions of a landslide affecting planned highway infrastructure in southeastern Xizang. Safety factors of 1.25, 1.07, and 1.02 under normal operation, rainfall, and seismic excitation loads, respectively, reveal the inadequacy of intrinsic stability. Consequently, dynamic compaction and chemical grouting techniques are assessed via simulation. An optimal strategy, entailing 6-m-deep densification at the highway location with 10% silica fume enhancement of 66.3% of the landslide area and 50.8% of the soil-bedrock interface, results in safety factors of 1.70, 1.49, and 1.23 for the three scenarios. The improved area is minimized to streamline construction practicality and economics while preserving geotechnical integrity. The integrated modeling outcomes demonstrate the model's capability in capturing localized incremental damage and the efficacy of numerical simulation for stability diagnosis and targeted remediation of intricate landslides. Advancements in constitutive relations development are vital for further innovation in geohazard evaluation and infrastructure safety assurance.